BEING UNSTUCK IN TIME: INTERPRETING THE DEICTIC SHIFT IN KURT VONNEGUT’S SLAUGHTERHOUSE FIVE - Yudho Sulistyo , Nikodemus (Jurnal Ilmiah Spectral, 2020)
Thérèse Raquin is a classic novel which is considered for years to have a dark yet natural story. The emotion and characterization are somewhat real. Therefore, the depiction of the characters and their lives is also real and natural. The bad and dark side of human’s life in this novel was controversial in the author’s time, Émile Zola. Thus, the writer finds out the necrophilic desires as one of the kind of sexual disorders seen in one of the main character’s characterization, Laurent Le Claire. The writer used psychoanalysis theory in digging necrophilic desires in the unconscious of Laurent through his acts and characterization. The writer also described Laurent’s past and his relationship to his father in order to prove his necrophilic desire.